2005
DOI: 10.1007/s00383-005-1517-3
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal detection of isolated gastric duplication cyst

Abstract: We present a rare case of gastric duplication cyst that was suspected prenatally. A routine prenatal ultrasonography (US) showed an abdominal cyst with peristalsis and a provisional diagnosis of enteric duplication was made. A healthy male infant was born at 39 weeks gestation and postnatal US identified a cyst, 5x3x2 cm in size, adjacent to the pancreas. At laparotomy, a cyst was found located in the lesser sac, but completely separated from the stomach, and partially adhered to the body of the pancreas and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…The term alimentary tract duplication is used for congenital lesions having three characteristics: [1] the presence of a well-developed coat of smooth muscle; [2] an epithelial lining representing some portion of the intestinal tract mucosa; and [3] intimate anatomic association with some portion of the gastrointestinal tract [1]. Recently, as we reported in the present case, congenital cystic lesions having gastrointestinal epithelial and wall characteristics without an anatomic association with the alimentary tract have been reported and described as ''isolated duplication'' or ''completely isolated duplication'' of the alimentary tract; eight such cases have been previously reported in the literature [2][3][4][5][6][7]. All but one case was detected and treated during the neonatal period.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The term alimentary tract duplication is used for congenital lesions having three characteristics: [1] the presence of a well-developed coat of smooth muscle; [2] an epithelial lining representing some portion of the intestinal tract mucosa; and [3] intimate anatomic association with some portion of the gastrointestinal tract [1]. Recently, as we reported in the present case, congenital cystic lesions having gastrointestinal epithelial and wall characteristics without an anatomic association with the alimentary tract have been reported and described as ''isolated duplication'' or ''completely isolated duplication'' of the alimentary tract; eight such cases have been previously reported in the literature [2][3][4][5][6][7]. All but one case was detected and treated during the neonatal period.…”
Section: Discussionmentioning
confidence: 58%
“…Four previously reported cases [2,3,7], as well as the present case, were found to have an intraabdominal cystic lesion on prenatal ultrasound examination. The differential diagnosis of prenatal abdominal cystic lesions includes adrenal, renal, gastrointestinal, and lymphatic masses.…”
Section: Discussionmentioning
confidence: 66%
“…The presence of an ectopic gastric tissue in the lining of the cyst may result in lifethreatening hematemesis or hemoptysis if the cyst fistulates into the bronchus. The risk of bleeding was confirmed in the series of Foley et al [16] and Nakazawa et al [6]-the histopathologic examination of the cyst revealed gastric tissue with mucosal erosions. In our case, the surgical approach was advocated because of the space occupying effect of the cyst.…”
Section: Discussionmentioning
confidence: 80%
“…Prenatal detection of gastric duplication allows appropriate management and approach at birth. As far as we know, all previously detected gastric duplications were located in the abdomen [6][7][8][9]. We report what we believe is the first case of an isolated intrathoracic gastric duplication detected on a routine prenatal ultrasound examination.…”
mentioning
confidence: 72%
“…Imaging findings for malrotation and volvulus included midline stomach, small bowel on right side of the midline, classic mesenteric whirlpool sign (twisted mesentery around the mesenteric vascular stalk), coffee-bean sign, and three parallel fixed bowel loops on transverse scan (4,(6)(7)(8). Reported imaging findings for intestinal duplication cyst included thin-or thick-walled cystic structure, double wall appearance/sign, pseudo-double bubble appearance, abdominal cyst with peristalsis, echogenic mesenteric tissue consisting of fat close to the cyst, and intra-cystic echogenic contents (9)(10)(11)(12). Reported characteristics of meconium pseudocyst included thick membrane containing multiple calcium deposits and plaques (13).…”
Section: Answermentioning
confidence: 99%